2009
DOI: 10.1007/s10144-008-0137-x
|View full text |Cite
|
Sign up to set email alerts
|

Null model analyses of presence–absence matrices need a definition of independence

Abstract: Tests for species interactions that involve the comparison of a statistic calculated from observed matrix of species presences and absences with the distribution of the same statistic generated from a null model have been used by ecologists for about 30 years. We argue that the validity of these tests requires a specific definition of independence. In particular, we note that an assumption that is often made is that all presence-absence matrices with the same row and column totals are equally likely if there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In the first, the probability of converting a matrix element from 0 to 1 was based on the formula for null 8 in Table I, p ( X ij ) = S i T j / N 2 . Gotelli ( 15 ) is clear to indicate that this probability applies strictly to the first entry, and so this method is designated “null 8.” The second approach uses a statistical fitting procedure of Navarro‐Alberto and Manly ( 22 ) to derive p ( X ij ), designated “null 8 NM.” These authors note that the underlying species abundance data may be modeled with a log‐linear model where the expected value of abundance E ( A ij ) is given by a constant overall effect γ, a species effect δ j , and a location effect ϑ i . : …”
Section: Methodsmentioning
confidence: 99%
“…In the first, the probability of converting a matrix element from 0 to 1 was based on the formula for null 8 in Table I, p ( X ij ) = S i T j / N 2 . Gotelli ( 15 ) is clear to indicate that this probability applies strictly to the first entry, and so this method is designated “null 8.” The second approach uses a statistical fitting procedure of Navarro‐Alberto and Manly ( 22 ) to derive p ( X ij ), designated “null 8 NM.” These authors note that the underlying species abundance data may be modeled with a log‐linear model where the expected value of abundance E ( A ij ) is given by a constant overall effect γ, a species effect δ j , and a location effect ϑ i . : …”
Section: Methodsmentioning
confidence: 99%
“…However, very different types of association might be called random with respect to certain factors. Even with a precisely stated null hypothesis about randomness, it is still uncertain whether an associated randomization adequately approximates the pattern predicted by the null hypothesis (Navarro‐Alberto and Manly 2009).…”
Section: Benchmark Metric and Algorithm Performance In Null Model mentioning
confidence: 99%
“…For very large matrices, and for matrices sampled at large spatial scales, the homogeneity assumption cannot be justified and traditional null models should be applied with caution. Recently Navarro‐Alberto and Manly (2009) showed that any difference either in occurrence probabilities of species across sites (non‐uniform column degree distributions) or species (non‐uniform row degree distributions) causes some degree of spatial autocorrelation. Null models that do not correct for autocorrelation may therefore too often point to non‐randomness.…”
Section: Sample Size Effects In Null Model Analysismentioning
confidence: 99%
“…No algorithm produces every possible matrix during the randomization, except perhaps for the smallest of matrices. This issue of biased randomizations has recently attracted the attention of ecologists and statisticians (Zaman & Simberloff, 2002;Miklós & Podani, 2004;Lehsten & Harmand, 2006;Navarro-Alberto & Manly, 2009;Sanderson et al, 2009;Fayle & Manica, 2010;Gotelli & Ulrich, 2011). In a greater context, the use of data randomization (as a null model and statistical test of inference) is not distribution-free.…”
Section: Introductionmentioning
confidence: 99%